Postinfectious Optic Neuritis After Hand–Foot–Mouth Disease. Issue 3 (September 2021) - Barrett, Spencer C.; Bhat, Nita N.; Bindiganavile, Shruthi H.; Lee, Andrew G.
Abstract : Abstract: A 33-year-old man presented with acute painless loss of vision in his right eye after hand–foot–mouth disease (HFMD). Examination confirmed a right optic neuropathy. Neuroimaging and routine evaluations for alternative causes for an optic neuropathy were negative. He was treated with high dose corticosteroids and made an almost complete visual recovery. Postinfectious optic neuritis has been reported after a vast array of infections including: varicella zoster virus, influenza virus, herpes simplex virus, Epstein–Barr Virus, Lyme disease, and many others. Although Coxsackie virus infections are a known cause of HFMD and have been reported to cause maculopathy, to the best of our knowledge, this is the first reported case of optic neuritis after HFMD in the English language ophthalmic literature.